2022
DOI: 10.1155/2022/9009406
|View full text |Cite|
|
Sign up to set email alerts
|

Efficient COVID-19 CT Scan Image Segmentation by Automatic Clustering Algorithm

Abstract: This article addresses automated segmentation and classification of COVID-19 and normal chest CT scan images. Segmentation is the preprocessing step for classification, and 12 DWT-PCA-based texture features extracted from the segmented image are utilized as input for the random forest machine-learning algorithm to classify COVID-19/non-COVID-19 disease. Diagnosing COVID-19 disease through an RT-PCR test is a time-consuming process. Sometimes, the RT-PCR test result is not accurate; that is, it has a false nega… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 31 publications
0
4
0
Order By: Relevance
“…and Gupta S.K. [ 24 ] addressed automated segmentation and classification of COVID-19 and normal chest CT scan images. They introduced a variant of the whale optimization algorithm named the improved whale optimization algorithm (IWOA).…”
Section: Introductionmentioning
confidence: 99%
“…and Gupta S.K. [ 24 ] addressed automated segmentation and classification of COVID-19 and normal chest CT scan images. They introduced a variant of the whale optimization algorithm named the improved whale optimization algorithm (IWOA).…”
Section: Introductionmentioning
confidence: 99%
“…Shivahare and Gupta 22 computed ideal multiple threshold value for multilevel COVID-19 CT scan image segmentation by improved whale optimization algorithm (IWOA). Better segmentation mask and segmentation accuracy were obtained for IWOA-based segmented images as compared to WOA, SSA, and SCA-based segmented images.…”
Section: Introductionmentioning
confidence: 99%
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [ 1 ]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process: Discrepancies in scope Discrepancies in the description of the research reported Discrepancies between the availability of data and the research described Inappropriate citations Incoherent, meaningless and/or irrelevant content included in the article Peer-review manipulation …”
mentioning
confidence: 99%
“…Tis article has been retracted by Hindawi following an investigation undertaken by the publisher [1]. Tis investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process:…”
mentioning
confidence: 99%